Pengaruh Variasi Arus Pengelasan Kombinasi GTAW dan SMAW terhadap Sifat Mekanik pada Carbon Steel A53 GR B - Hamdani Hamdani; Adi Saputra Ismy; Muhammad Rizki (Politeknik Negeri Lhokseumawe, 2022)
The piping system in process industry plays an important role and generally is connected by welding where the welding uses a certain current, therefore this study analyzes the appropriate current variation for welding combinations between GTAW and SMAW on A 53 GR B material using 3 variations of currents, namely 70A, 100A, and 120A. The results of the stable hardness test occurred in specimens with a holding time of 20 seconds with a hardness value of 33.67 HRC on base metal 1, on HAZ 1 of 36.00 HRC, 38.83 HRC on weld metal, 38.83 HRC on HAZ 2, on base metal 2 of 32.00 HRC. The value of the impact energy of the A3 specimen with a value of 142 joules and an impact value of 3.55 j/mm2, The value of the impact value of the B3 specimen with a value of 92 joules and an impact value of 2.30 j/mm2.